2015
DOI: 10.1002/2014jd022834
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of black carbon‐containing particles from soot particle aerosol mass spectrometer measurements on the R/V Atlantis during CalNex 2010

Abstract: We present mass spectrometry measurements of black carbon-containing particles made on board the R/V Atlantis during the CalNex (California Research at the Nexus of Air Quality and Climate Change) 2010 study using an Aerodyne Research Inc. soot particle aerosol mass spectrometer (SP-AMS). The R/V Atlantis was deployed to characterize air masses moving offshore the California coast and to assess emissions from sources in urban ports. This work presents a first detailed analysis of the size-resolved chemical com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
64
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(68 citation statements)
references
References 72 publications
3
64
1
Order By: Relevance
“…These findings have important implications for obtaining quantitative mass measurements and can help to better inform the analysis and interpretation of SP-AMS measurements of the emissions and aging of BBA Dallmann et al, 2014;Fortner et al, 2012;Lee et al, 2016;Massoli et al, 2015). We would like to add, however, that although changes in d va may result in varying E IR , SP-AMS measurements of rBC have been shown to correlate with reference measurements Willis et al, 2014).…”
Section: Resultsmentioning
confidence: 93%
“…These findings have important implications for obtaining quantitative mass measurements and can help to better inform the analysis and interpretation of SP-AMS measurements of the emissions and aging of BBA Dallmann et al, 2014;Fortner et al, 2012;Lee et al, 2016;Massoli et al, 2015). We would like to add, however, that although changes in d va may result in varying E IR , SP-AMS measurements of rBC have been shown to correlate with reference measurements Willis et al, 2014).…”
Section: Resultsmentioning
confidence: 93%
“…The average ratio drops to about 1.05 if the three major oxygenated organic fragments, including CO + , CO + 2 , and C 2 H 3 O + , are also excluded in the calculation. Using the same measurement approach and R BC -dependent CE, Massoli et al (2012Massoli et al ( , 2015 reported that 81 and 87 % of HOA was associated with rBC particles near vehicular emissions and in a polluted offshore environment.…”
Section: Comparisons Of Nr-pm Rbc and Nr-pm Componentsmentioning
confidence: 99%
“…Real-time and mass-based chemical compositions of organic coatings on ambient BC particles were seldom reported until the recent development of an Aerodyne soot-particle aerosol mass spectrometer (SP-AMS; Cappa et al, 2012;Massoli et al, 2012Massoli et al, , 2015Onasch et al, 2012;Liu et al, 2015;Lee et al, 2016;Willis et al, 2016). In this study, we investigate formation of organic coatings on BC particles by deploying a SP-AMS in Fontana, California, which is located in the broader South Coast Air Basin and includes the greater Los Angeles area.…”
Section: Introductionmentioning
confidence: 99%
“…However, the debate on the absorption enhancement capacity of rBC-containing particles is still ongoing, because discrepancies exist between observations and theoretical predictions based on Mie scattering models (Shiraiwa et al, 2010;Cappa et al, 2012) and among observation results from different locations and using different sources (Healy et al, 2015;S. Liu et al, 2015;Massoli et al, 2015;Ueda et al, 2016). The widely accepted explanations are as follows.…”
Section: Introductionmentioning
confidence: 99%